Analisa Ketidak Seimbangan Beban Terhadap Arus Netral Dan Losses Pada Transformator Distribusi Di Gedung Fakultas Teknik Universitas Riau - Fahrurozi, Fahrurozi; Firdaus, Firdaus; Feranita, Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Load Imbalancing in power distribution system that has been occurred either by inconstant load factor in its phase or power on with diffrent period. The consequences of Load Imbalancing is current appears in neutral trafo and losses cannot avoid. Decreasing quality of voltage and current, trafo efficiency, enegy measuring is loss that caused. voltage and Current quality is going decrease due to 0 current distort basic wave until bad. Keywords: loadimbalance, losses, and neutral current.